Pengaruh Penambahan HHO terhadap Kinerja dan Ionisasi Pembakaran Motor Bensin - Akbar, Ali; Wardana, ING; Yuliati, Lilis (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2014)
This aim of this research was to conduct the effect of HHO which injected into the combustion chamber through the intake manifold of the gasoline four-stroke motorcycle engine. HHO is a mixture of hydrogen and oxygen was produced by water electrolysis process.The experiments were carried out by using the HHO generatorin intake manifold to produced HHO gas, which injected into the combustion chamber. The HHO gas injection was varied of 0 ml/s, 0.75 ml/s, 1.5 ml/s, 2.25 ml/s and 3 ml/s based on the engine shaft revolution (rpm). The engine shaft revolutions were also varied at 1700 rpm, 2200 rpm, 2700 rpm, 3200 rpm, 3700 rpm, and 4200 rpm. The engine performance (power output effectively, SFC, and thermal efficiency), the ionization combustion (burning voltage and burning time) and exhaust gas emissions (HC and CO) were investigated. The results show that the additionof the HHO gascould improve the performance of the gasoline four-stroke engine. The effective of power out-put and thermal efficiency increase as increase the HHO injection.The specific fuel consumption (sfc) was also decreases as increases the HHO injection. The ionization combustion much better, which the voltage products of combustion increase and combustion time decrease as increase the HHO injection. The addition of HHO gas was also improved the quality of exhaust gas emission which are reduce the content of CO and HC gases due tothe HHO enhance the combustion process. The hydrogen gas has a high diffusivity which can improve of the fuel mixing, turbulence and homogeneity. The hydrogen gas has the flamehigh faster than gasoline, therefore its decrease the burning time as increase the HHO injection.Keywords: HHO, Hydrogen, Ionization, Gasoline Engine, Emissions